Ferdinand Magellan : and the first voyage around the world - Gallagher, Jim, 1969- (Philadelphia, PA : Chelsea House, 2000)
Presents a biography of the daring Portuguese sea captain who commanded the first expedition that sailed around the world.
Includes bibliographical references (p. 62 ) and index.
School Library Journal, July 2000.
School Library Journal.
6.7
5-8
Keywords: d; Magellan, Ferdinand, -- -1521.; Magellan, Ferdinand, -- -1521.; Explorers -- Portugal -- Biography -- Juvenile literature; Voyages around the world -- Juvenile literature; Explorers; Voyages around the world; Explorers -- Biography; Voyages around the world; Explorers -- Biography; Voyages around the world